Valuation of Business and Factors Impacting The Demand for Istano Basa Pagaruyung Cultural Tourism - Fadhila Hukmi; Nimmi Zulbainarni; Siti Jahroh (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
Istano Basa Pagaruyung is a famous cultural attraction in West Sumatra. The attractiveness potentials of Istano Basa Pagaruyung that is unique, beautiful, and visited by many tourists, is a supporting factor for optimizing the management of Istano Basa Pagaruyung's attraction. The addition of buildings and supporting facilities to support tourism objects and the increase of entrance tickets for Istano Basa Pagaruyung made it necessary to identify the valuation of the tourist attraction business. This study aimed to analyze the perception of visitors on Istana Baso Pagaruyung cultural tourism and its economic value estimation. The economic value of Istano Basa Pagaruyung in terms of tourist demand was estimated using the Travel Cost Method (TCM) approach. Data were obtained using questionnaires disseminated to the visitors. The results showed that the cost of travel, level of education, and length of knowing the location significantly affected the level of visits to Istano Basa Pagaruyung. Based on the calculation, the consumer surplus based on the individual travel cost method was Rp29,395.00 per individual per visit and the economic value of the location was Rp11,622,500,583.00. The large economic benefits of tourism activities in Istano Basa Pagaruyung had a positive influence on the socioeconomic improvement of the local people Keywords: travel cost method, economic valuation, cultural tourism